EVALUATION OF STAFFING STRENGTH OF COLLEGES OF EDUCATION IN NIGERIA - Suleiman, Hamza Alhaji (Sokoto Educational Review, 2015)
This study evaluated the staffing strength of Colleges of Education in Nigeria. The survey research design was employed. The population was made of four groups that comprised of all the management staff of the colleges 528, all the academic staff 3684, all the non-academic staff 9101 and all the senior staff of the National Commission for Colleges of Education (NCCE) 86 totaling to 13,399. Using both randomization and random stratified sampling techniques a rounded sample of 1000 respondents were selected and used. The distribution was a total of 156 Management staff, 410 Academic staff, 409 Non-academic staff and 25 NCCE officials. A structured questionnaire on five point Likert rating scale was administered. The null hypothesis was tested using One-way Analysis of Variance (ANOVA). A post-hoc Schaffers’ test was conducted that showed the extent of their difference. The findings of the study indicated that staffing strength is inadequate more especially when compared to the NCCE stipulated staff-student ratios. Therefore, recommendations include a massive recruitment of academic staff and an urgent implementation of the migration accord of condition of service of these colleges to that of the university nation-wide.